Área de poliedros no cotidiano - Villas Boas, Fernando Cleber [UNESP] (2014)
The study of this work is concentrated on the concept of area of polyhedra using planning. Initially we give the theoretical basis, then we present a sequence of activities that familiarize students with polyhedra, presenting examples of their daily lives, inducing them to identify theirs characteristics, teaching them to classify them, to relate the polyhedral surfaces to representations in the plan and to work the area concept of polyhedra through this relationship. To conclude we present problems situations in the daily lives, as application of this concept